Analysis of Leg Strength and Power of Soccer Academy Students: A Review of Playing Positions - Nur Azmi, Dina Aprilia; Anam, Khoiril (Journal of Physical Education Health and Sport, 2023)
This study aims to determine the ability of arm muscle strength, abdominal muscle strength, and bond strength. The type of research used in this research is survey research with test and measurement techniques. The data analysis technique used is descriptive analysis. The research results show that; (1) the ability of the arm muscle strength of the football academy students shows an average score of 5.1 and is in the less category with a total of 13 students and a proportion value reaching 36%. which is played by 5 students with the position of the forward player and 5 students as the back player; (2) the abdominal muscle strength ability of the football academy students showed an average score of 29 and was in the good category with a total of 26 students and the proportion of scores reaching 72% which was dominated by 10 students with defender positions; (3) the carrying capacity of the football academy students shows an average score of 208.6 and is in the medium category with a total of 19 students and the proportion of scores reaching 53% which is dominated by 8 students with defender positions.